Estimation of Single Hour Emission Rate From Marine Traffic In Batam-Singapore Waterways Using Automatic Identification System (AIS) Data - Hendra Saputra; Nidia Yuniarsih; Naufal Abdurrahman; Mufti Fathonah Muvariz; Sapto Wiratno S; Tri Ramadani Arjo (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2019)
This paper focuses on estimation of single hour emission rate from ships traffic in the Batam-Singapore waterways as it is one of the congested narrow straits area used for international shipping. MEET methodology is used to estimate emissions from ships.There were 1326 total number of ships through the strait at 22.00 on September 4, 2018 produces total exhaust emission for NOx, CO, CO2, VOC, PM and SOx were about 48,716.48 kg/hour, 62,297.39 kg/hour, 3,541,656.53 kg/hour, 14,751.79 kg/hour, 1,339.14 kg/hour and 22,319.03 kg/hour, respectively. This paper also try to compare the result of emission calculated on previous research of single hour emission rate on 2011, 2014 and the current results. The result of comparison shows that there is a significant difference of CO2 emission results.